Longitudinal evaluation of treatment patterns, risk factors and outcomes in patients with cardiovascular disease treated with lipid-lowering therapy in the UK. Issue 4 (29th April 2022) - Danese, Mark; Sidelnikov, Eduard; Villa, Guillermo; Catterick, David; Iqbal, Mazhar; Gleeson, Michelle; Lubeck, Deborah; Patel, Jeetesh
Abstract : Objectives: To compare treatment patterns, risk factors and cardiovascular disease (CVD) event rates in the UK from 2008 to 2017. Design: Retrospective cohort study using the Clinical Practice Research Datalink. Setting: UK primary care. Participants: We selected 10 annual cohorts of patients with documented CVD receiving lipid-lowering therapy and the subsets with myocardial infarction (MI). Each cohort included patients ≥18 years old, with ≥1 year of medical history and ≥2 lipid-lowering therapy prescriptions in the prior year. Primary and secondary outcome measures: For each annual cohort, we identified cardiovascular risk factors and lipid-lowering therapy and estimated the 1-year composite rate of fatal and non-fatal MI, ischaemic stroke (IS) or revascularisation. Results: The documented CVD cohort mean age was 71.6 years in 2008 (N=173 424) and 72.5 (N=94 418) in 2017; in the MI subset, mean age was 70.1 years in 2008 (N=38 999) and 70.4 in 2017 (N=25 900). Both populations had larger proportions of men. In the documented CVD cohort, the proportion receiving high-intensity lipid-lowering therapy from 2008 to 2017 doubled from 16% to 32%; in the MI subset, the increase was 20% to 48%. In the documented CVD cohort, the proportion of patients with low-density lipoprotein cholesterol (LDL-C) <1.8 mmol/L increased from 28% to 38%; in the MI subset, the proportion with LDL-C <1.8 mmol/L increased from 32% to 42%. The composite event rate per 100 person-years declined over time, from 2.5 to 2.0 in the documented CVD cohort, and from 3.7 to 2.8 in the MI subset. After excluding revascularisation from the composite outcome, the decline in the event rate in both populations was substantially attenuated. Conclusions: Despite an increase in high-intensity therapy use and a decline in revascularisation, more than half of patients did not receive high-intensity lipid-lowering therapy by 2017 and incidence rates of MI and IS remained virtually unchanged.